Śāntideva and the Transformation of Mind: The Interdependence of Ethics and Wisdom, with Reference to the Perfection of Generosity - Jeyapalasingham, Puthiran (Université d'Ottawa | University of Ottawa, 2025)
This thesis argues that Śāntideva’s ethics consists of a transformation of mind. We demonstrate this interpretation by presenting a mind-training framework of Śāntideva’s ethics, with a specific focus on the perfection of generosity. Generosity is a quality of the mind (citta), and to cultivate the mind of generosity, the bodhisattva trains his mind to attain wisdom. Upon attaining wisdom, the bodhisattva’s mind is transformed, and he possesses the perfected perfection of generosity. The mind-training framework thus shows an interdependence between ethics and wisdom. The mind-training framework is demonstrated by first explaining the pertinence of this interpretation; this requires contextualizing Śāntideva’s ethics within the scope of bodhicitta. Based on this context, we argue that Śāntideva’s ethics must be understood from the standpoint of aspirational bodhicitta. This standpoint reveals the importance of cultivating the perfections with an aim to attain wisdom. To further explain the pertinence of the mind-training framework, we examine competing interpretations of Śāntideva’s work and expound their difficulties. Having addressed various interpretations of Śāntideva’s ethics, we then discuss the mind-training framework. We present this framework with reference to a topic that has not received much attention in current scholarship: we refer to a specific training for the bodhisattva, which is introduced in Śāntideva’s Śikṣāsamuccaya. This training shows that to cultivate the mind of generosity, the bodhisattva must cultivate the other perfections in sequence with the goal of attaining wisdom. We then examine the nature of wisdom as described by Śāntideva in Chapter 9 of Bodhicaryāvatāra. Wisdom, for Śāntideva, is the realization that all persons and phenomena are empty (śūnya) of self-nature (svabhāva). Upon realizing this, the bodhisattva has a mind of generosity that is not clouded by ignorance; generosity is now perfected. Overall, by incorporating bodhicitta in an interpretation of Śāntideva, we aim to show that his ethics is best interpreted as a transformation of mind which reveals an interdependence between ethics and wisdom.
Keywords: Philosophy; Ethics; Indian Philosophy; Buddhist Philosophy; Buddhism; Buddhist Ethics